Deep Learning Approach in IPAS Instruction: Enhancing Elementary School Students’ Skills and Competencies - Nila Rosa; Masita Masita; Syahru Ramadhan (Universitas Islam negeri Mahmud Yunus Batusangkar, 2026)
This study aims to examine the implementation of IPAS learning through a deep learning approach in enhancing students’ skills and competencies at the elementary school level. IPAS learning requires instructional strategies that promote active student engagement while fostering higher-order thinking skills. This research describes how the deep learning approach is applied in the learning process and how it influences the development of students’ skills. The study employs a qualitative approach with a case study design. Data were collected through classroom observations, interviews with teachers and students, and analysis of instructional documents. Data analysis was conducted through data reduction, data display, and interpretative analysis to understand the dynamics of the learning process. The findings indicate that the implementation of a deep learning approach in IPAS learning creates a more active, reflective, and collaborative learning environment. Learning activities involving concept exploration, group discussions, and observation of real-life phenomena help students develop a deeper understanding of the subject matter. In addition, this approach contributes to the development of critical thinking skills, problem-solving abilities, and collaborative competencies among students. Instructional strategies that emphasize active participation and contextual learning experiences provide greater opportunities for students to construct meaningful conceptual understanding in IPAS learning.